The Effect of Ankle Sleeve Use on Football Player’s Running Performance - Prasetyo Catur Utomo; Dwi Setyawan; Salsa Ayu Lestari (Journal of Prosthetics Orthotics and Science Technology, 2026)
Background: Football players with high running speeds will also have strong football skills. Over 50% of running activities are attributed to the ankle and foot. Running speed can be maximized with strong ankles. To keep the ankles healthy when running, ankle sleeves might be provided. One type of support for the ankle that applies the proper amount of pressure without being overly rigid or strong is an ankle sleeve. Because the ankle sleeve's function can limit excessive range of motion movements, improve alignment prior to initial contact, alter neuromuscular activity, and provide additional support that can prevent excessive movement, it is anticipated that the ankle will remain in good condition when running. Aim: The purpose of this study is to ascertain how wearing ankle sleeves affects football player’s running speeds. Method: One group pretest and posttest design in quantitative research. Thirteen individuals who wore ankle sleeves for four weeks made up the research sample. The paired sample T test is used for data analysis. Results: p = 0.001 (<0.05) for the analysis test. Conclusion: Football players' running speeds are impacted by the use of ankle sleeve.